Comparative analysis of chemical constituents and bioactivities of the extracts from leaves, seed coats and embryoids of Ginkgo biloba L. Issue 23 (2nd December 2021) - Chen, Xuanxuan; Zhong, Wu; Shu, Changqing; Yang, Hong; Li, Erhu
Abstract: A total of 25 compounds including terpenoids, flavonoids, biflavonoids and ginkgolic acids were identified and quantified with a reliable, simple, and simultaneous method from Ginkgo leaves, seed coats and embryoids with different tree ages (approximately identified as 25, 500, 1000 and 2000 years). Leaves had the highest amount of total bioactive compounds. Seed coats had moderate contents of flavonoids, which was 15 times higher than embryoids. Furthermore, the effects of tree ages on bioactive compounds differ in three parts. The contents of bilobalide, ginkgolide J, ginkgolide C, ginkgolide B, ginkgolide A in embryoids and seed coats were highest from 500-year-old tree, while in leaves were highest from 25-year-old tree. This work first investigated the extensive bioactive compounds in ginkgo leaves, seed coats and embryoids from Ginkgo trees older than 500-year, it gives good reference for making better use of Ginkgo products. Graphical Abstract: